Analisi Faktor Risiko Malaria Di Wilayah Kerja Puskesmas Sarmi Kota, Kabupaten Sarmi, Tahun 2012 - Imbiri, James Khristian; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Several factors have potential to accommodate the spread and cause of malaria include environmental,physical, condition housing, and comunity behaviour. People in the working area of the Sarmi Municipal PublicHealth Service, Sarmi District, have high risk behavior of being exposed by malaria disease. In addition, physicalcondition of housings are still far below healthy standard. Slumps area and bushes around the environment understudy have contributed to poor health condition. The presence of cattle cages nearby the houses have been consideredto cause the vast growing malaria-bound mosquitos.Methode : This study aimed to find out the relationship between environmental conditions nearby the houses, physicalconditions, housing comunity behaviors and malaria incidence in the working area of Sarmi Municipal Public HealthService, Sarmi District, Sarmi Regency, Papua Province. This observational study applied a restropective study with acase control approach, in which case group – those who suffered from malaria – were compared with control group. Thecase group consisted of 57 respondents, whereas the control group consisted of 57 respondents. Data were subject tounivariate and bivariate analyses using a Chi-square technique. To calculate the risk factor, the study applied an oddratio and to find out the simultaneous relationship meaning (p) between independent variables and the dependentvariables the study applied a multivariate analysis. This analysis was then correlated with a logistic regression.Result : Results of the study showed the following outputs: 1) a relationship between water slumps and malaria (OR5.827); 2) a relationship between bushes and malaria (OR 3.232); 3) a relationship between window ventilation filtersand malaria (p value : 0.014; OR 2.773); and 4) a relationship between type of houses and malaria (OR 3.714).Conslusion : The study concluded that the presence of water slumps contributed to the growth of mosquito larvae.The malaria risk factors related to the installation of window ventilation filters, types of houses, and the presence ofbushes nearby the housings. These risk factors have affected the malaria incidence in the working area of SarmiMunicipal Public Health Center as much as 99.9%.Keywords : malaria, Environment, Physical Conditions Housing, and Behaviors.